2022
DOI: 10.32890/mjli2022.19.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Teachers’ Online Teaching Experience in Times of School Closures: The Case of Malaysia

Abstract: Purpose – Given that students were out of school in response to the COVID-19 pandemic public health measures, traditional teaching practices have been forced to switch to online mediated learning environments. This study represents the first research effort to capture the experience of Malaysian mathematics teachers about their teaching during the pandemic. This includes investigating digital education tools mathematics teachers used, issues they encountered, and the knowledge and skills they need to improve d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, there are studies found that teachers still lack the knowledge and skills to integrate technology in the classroom (Lee et al, 2006). Furthermore, a quantitative study conducted by Chin et al (2022) also found that 50% of the study's respondents expressed the need for improvement in teaching technology skills compared to other skills such as management, communication, and instructional planning. Other than that, a study conducted by Poobalan and Safwan (2022) has indicated that primary school Mathematics teachers face several constraints in implementing the use of technology, such as lack of technological resources, time constraints, and limited knowledge regarding the latest technology for instructional purposes.…”
Section: Literature Review Technology In the Malaysian Primary Educat...mentioning
confidence: 98%
See 1 more Smart Citation
“…However, there are studies found that teachers still lack the knowledge and skills to integrate technology in the classroom (Lee et al, 2006). Furthermore, a quantitative study conducted by Chin et al (2022) also found that 50% of the study's respondents expressed the need for improvement in teaching technology skills compared to other skills such as management, communication, and instructional planning. Other than that, a study conducted by Poobalan and Safwan (2022) has indicated that primary school Mathematics teachers face several constraints in implementing the use of technology, such as lack of technological resources, time constraints, and limited knowledge regarding the latest technology for instructional purposes.…”
Section: Literature Review Technology In the Malaysian Primary Educat...mentioning
confidence: 98%
“…Referring to the content of the primary school Mathematics curriculum, teachers are advised to apply various types of technology to enhance students' understanding and encourage them to be active learners (MOE, 2021). Past studies have discussed the effectiveness of technology integration as a supportive tool in Mathematics education, offering new experiences to both teachers and students (Chin et al, 2022). Parrot and Leong (2018) also found that technology can assist teachers in creating a learning environment that focuses on visualising abstract ideas as well as organising and analysing data.…”
Section: Literature Review Technology In the Malaysian Primary Educat...mentioning
confidence: 99%
“…They also faced difficulties in monitoring student progress and providing timely feedback, which is essential components of effective teaching and learning (Sim et al, 2021). Furthermore, teachers were expected to adopt new pedagogical approaches while overcoming their own technological limitations (Jiew et al, 2022). The lack of face-to-face interaction also had a negative impact on student motivation and led to an increase in instances of academic dishonesty (Wahab et al, 2022).…”
Section: Home-based Teaching and Learning (Pdpr) In Malaysiamentioning
confidence: 99%
“…They concluded that virtual teaching strategies have a big effect on college students' overall performance. As per Chin et al (2022) understudies were out of school because of the Coronavirus pandemic and general well-being measures, conventional showing rehearses have been compelled to change to online interceded learning environments. Then, her two most normal issues looked at by overviewed educators were web issues and understudy association during internet learning.…”
Section: Virtual Teaching Techniquementioning
confidence: 99%